2022
DOI: 10.1007/s00429-022-02592-w
|View full text |Cite
|
Sign up to set email alerts
|

In mice and humans, brain microvascular contractility matures postnatally

Abstract: Although great efforts to characterize the embryonic phase of brain microvascular system development have been made, its postnatal maturation has barely been described. Here, we compared the molecular and functional properties of brain vascular cells on postnatal day (P)5 vs. P15, via a transcriptomic analysis of purified mouse cortical microvessels (MVs) and the identification of vascular-cell-type-specific orpreferentially expressed transcripts. We found that endothelial cells (EC), vascular smooth muscle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We next sought to determine which mRNAs were localized to PvAPs during postnatal development. We recently described the transcriptome of mechanically purified dorsal cortex MVs on P5 and P15 (Slaoui et al, 2023) (Figure 3a). Since PvAPs stay attached to mechanically purified MVs, we leveraged our knowledge of this transcriptome to detect changes over time in MV's mRNAs that are selectively or specifically expressed in astrocytes (and thus potentially present in PvAPs), according to recently published single‐cell RNA sequencing (RNASeq) datasets for adult brain vascular cells (He et al, 2016; Vanlandewijck et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next sought to determine which mRNAs were localized to PvAPs during postnatal development. We recently described the transcriptome of mechanically purified dorsal cortex MVs on P5 and P15 (Slaoui et al, 2023) (Figure 3a). Since PvAPs stay attached to mechanically purified MVs, we leveraged our knowledge of this transcriptome to detect changes over time in MV's mRNAs that are selectively or specifically expressed in astrocytes (and thus potentially present in PvAPs), according to recently published single‐cell RNA sequencing (RNASeq) datasets for adult brain vascular cells (He et al, 2016; Vanlandewijck et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…RNASeq data were analyzed as described previously (Slaoui et al, 2023). The RNASeq gene expression data and the raw fastq files are available on the GEO repository (http://www.ncbi.nlm.nih.gov/geo/), with the accession number GSE173844.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maturation of the brain primary vascular network involves the recruitment of mural cells (VSMCs and pericytes), establishment of the BBB properties (barriergenesis), the generation of the extracellular matrix, and enwrapping by astrocytic endfeet. Cerebral arteries undergo refinement until the third postnatal month [[40]] as studies have shown that arteriolar VSMC expands and matures during this period and becomes contractile to better control cerebral blood flow [[41]]. Astrocytic recruitment and differentiation occurs during the late embryonic and early postnatal periods [[42]].…”
Section: Origin and Maturation Of The Brain Vasculaturementioning
confidence: 99%